1989
DOI: 10.1093/oxfordjournals.ndt.a091874
|View full text |Cite
|
Sign up to set email alerts
|

The Use of an Amino-acid-based CAPD Fluid over 12 Weeks

Abstract: Eight patients with end-stage renal failure (plasma albumin less than 35 g/l) who were established on glucose CAPD exchanges, were studied for 4-week periods before, and after 12 weeks when 1% amino-acid solution had been used for the morning exchange. Anthropometric, biochemical, clinical and dietary assessments were made every 4 weeks. Dietary intakes of protein and calories were maintained. Studies with amino-acid solutions showed a mean of 13% and 8% amino acids remaining in the dialysate after 6 and 8 h r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 0 publications
1
35
1
Order By: Relevance
“…[21] Patients in the present study were selected according to their PD type, and no difference was observed according to their nutritional status. Also, the amino acidbased PD fluid used in this study differed in chemical composition from that of the fluid used by Young et al [18] and Bruno et al [19] in that it had a higher (1.1%) amino acid content, a higher osmolality (365 mosm/L), and was more biocompatible (lactate content 40 mmol/L, pH 6.7). These findings are in agreement with four other smaller studies.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…[21] Patients in the present study were selected according to their PD type, and no difference was observed according to their nutritional status. Also, the amino acidbased PD fluid used in this study differed in chemical composition from that of the fluid used by Young et al [18] and Bruno et al [19] in that it had a higher (1.1%) amino acid content, a higher osmolality (365 mosm/L), and was more biocompatible (lactate content 40 mmol/L, pH 6.7). These findings are in agreement with four other smaller studies.…”
Section: Discussionmentioning
confidence: 88%
“…Two studies reported a decrease in plasma cholesterol. [18,19] In one of these studies, there was no change in serum triglycerides over 12 weeks, [18] whereas a rise in serum triglycerides has been reported by another study. [20] In the present study, although serum triglyceride and cholesterol levels of patients on amino acid-based PD were lower than glucose-based PD, this was not significant.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In continuous ambulatory PD (CAPD) patients, amino acid (AA)-containing dialysate has been used to compensate for a low dietary protein intake and loss of AA and proteins through peritoneal clearance (10). Until now, however, no convincing clinical benefits have been demonstrated (11)(12)(13)(14)(15)(16)(17)(18)(19). AA dialysate may lead to significant increase in serum urea levels (11)(12)(13)(14) and metabolic acidosis (11,12,15), a protein catabolic stimulus (20,21).…”
mentioning
confidence: 99%
“…When well-balanced AA solutions were given together with a high caloric meal, the administration of AA-containing dialysate improved nutritional parameters, including an increase in serum proteins [146], normalization of plasma AA profile [150], increase in nitrogen balance [151] and weight gain [150] in malnourisched patients. In most studies, nitrogen excretion and plasma urea increased simultaneously, suggesting that a large part of the absorbed AAs are directly oxidized and used to sustain resting energy expenditure [150, 152, 153, 154, 155]. Intraperitoneal AA administration can also aggravate metabolic acidosis [150, 152, 153, 155] leading to defective incorporation into muscle and immediate oxidation.…”
Section: Treatment With Aasmentioning
confidence: 99%